1986
DOI: 10.1093/jac/17.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Macrolides and immunity: effects of erythromycin and spiramycin on human mononoclear cell proliferation

Abstract: Macrolides are actively concentrated by leucocytes. The dose-effect responses of spiramycin (Sp) and erythromycin (Er) on phytohaemagglutinin (PHA) and pokeweed mitogen (PWM) stimulated human mononuclear leucocytes (MNL) were studied. Cell viability was not altered at any antibiotic concentration (1-100 mg/l). Both Sp and Er showed dose-related inhibition of the proliferative response of PHA and PWM stimulated MNL. Very marked effects were observed at high antibiotic concentrations and the effects observed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…Furthermore, their different pharmacokinetic properties, especially with respect to their biological half-lives and intracellular concentrations at a given time (9,16,27,28), could explain their differential effects on IL-6 production within the same group. Indeed, differences in their interactions with phagocytes have already been shown (24,32). This is the first time, to our knowledge, that an antibiotic has been shown to increase IL-6 production.…”
Section: Resultsmentioning
confidence: 62%
“…Furthermore, their different pharmacokinetic properties, especially with respect to their biological half-lives and intracellular concentrations at a given time (9,16,27,28), could explain their differential effects on IL-6 production within the same group. Indeed, differences in their interactions with phagocytes have already been shown (24,32). This is the first time, to our knowledge, that an antibiotic has been shown to increase IL-6 production.…”
Section: Resultsmentioning
confidence: 62%
“…The results of these studies demonstrate that EM suppressed human lymphocyte proliferation in vitro (22,33).…”
Section: Methodsmentioning
confidence: 70%
“…Although the mechanism of the efficacy is uncertain, several hypotheses have been proposed, such as the immunomodulatory action of macrolide antibiotics. Macrolide antibiotics modulate the functions of inflammatory cells such as polymorphonuclear leukocytes, lymphocytes and macrophages (1,33). In addition, macrolide antibiotics directly affect airway secretory cell (12) and epithelial cell (35) functions.…”
mentioning
confidence: 99%
“…20 Other macrolides such as erythromycin have been shown to inhibit hypertrophic and metaplastic changes of goblet cells in rat nasal epithelium, as well as inhibit the proliferation of human mononuclear cells. 21,22 Azithromycin along with clarithromycin are reported to induce apoptosis of activated lymphocytes. 23 In previous studies in our laboratory, azithromycin was also observed to cause reversible autophagy in rabbit tracheal SMCs, but not apoptosis, as well as reversible inhibition of the proliferation.…”
Section: Discussionmentioning
confidence: 99%